Small channel-length SiC nanowire field-effect transistors - TEKER, KAŞİF (My University, 2021)
NM03.10.12 Small Channel-Length SiC Nanowire Field-Effect Transistors Ali Uzun and Kasif Teker; Electrical and Electronics Engineering, Istanbul SehirUniversity, Istanbul, Turkey.Low-dimensional semiconductor materials offer new ways to develop nanoscaleelectronic and optoelectronic devices and components. From the class of wide band gap semiconductor nanomaterials, SiC nanowires combine the uniqueproperties of one-dimensional materials with that of superior intrinsic SiC characteristics and offer great opportunities for high power and high frequencyelectronic devices as well as in sensors capable of operating at high temperatures or hostile environments.This study presents a systematic investigation of electronic transport properties of p-type SiC nanowire field effect transistors (SiCNW-FET) with multiplechannel lengths (smallest channel length SiCNW-FET reported). The investigation has focused on the parameters including transconductance (gm), carriermobility (µh), ON-OFF current ratio (gating effect- Ion/Ioff). Further, a comprehensive comparison of our experimental measurements with the previouslyreported theoretical and experimental studies is presented.MOCVD-grown long SiCNWs with diameters about 60 nm are placed on a highly doped SiO2/Si substrate. The electrodes (Cr/Au: 3nm/100nm) aredefined by the e-beam lithography (EBL) with varying channel lengths of 120 nm, 220 nm and 1.5 µm followed by metal deposition through e-beamevaporation. The initial electrical measurements from the fabricated p-type SiCNW-FETs exhibited transconductance of 6.9x10-9 A/V (@ Vds = 0.05V),carrier mobility of 1.7 cm2/V.s, carrier concentration (nh) of 3.72 x 1020 cm-3, and Ion/Ioff ratio more than 104 for a device with 120nm channel length. Thegating effect achieved in this study is the highest value reported in the literature for a SiCNW-FET, to the best of our knowledge. As a consequence, thisstudy shows the great potential of SiCNW-FETs to be utilized in nanoelectronic and nanophotonic applications.
Keywords: Metalurji ve Malzeme Mühendisliği; Mühendislik ve Teknoloji; Metallurgical and Materials Engineering; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; METALURJİ VE METALURJİ MÜHENDİSLİĞİ; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; METALLURGY & METALLURGICAL ENGINEERING